Produção do cuidado da equipe de enfermagem aos usuários de álcool e outras drogas na rede de atenção psicossocial - Carvalho, Priscilla Mecia Conceição (2018)
This study aimed to analyze the production of nursing team care to alcohol and other drug users in the RAPS in a municipality in the interior of Bahia and to map the devices used by the nursing team to produce care as well as to describe the actions of the nursing team to users of alcohol and other drugs in the services that comprise RAPS. For this, we take as theoretical reference the construction of the historical process of care for alcohol and other drug users and nursing from the perspective of the production of care in RAPS. The methodological trajectory chosen was the qualitative, in a critico-analytical perspective, was performed in a medium-sized municipality, in services that make up the RAPS (CAPS, CAPSAD, 01 Centro de Saúde). It was used semi-structured interview, systematic observation and documentary analysis to collect data. Eleven nursing professionals participated to the study, of which five were nurses and six were nursing technicians. According to the analysis emerged the category: Devices for the production of care: mismatch between what is advocated and what is done.The nursing team's understanding of the production of care for users of alcohol and other drugs has moved between a "specific place" to take care of users, and the CAPS has been identified several times as the place where care should be taken and the lack of qualification to take care of users. When we approached the devices for the production of care, we saw that the users' access to the service happens through referrals and referrals, evidencing a fragmented and technicist work. Regarding the host, this demonstrates compliance with the first contact with the user, but in the activities developed for the reception of users and their families, it is pointed thatthe CAPS and CAPS AD services performed these activities. It was evidenced that the majority of professionals did not know about the PTS and the reference professional and the activities for the organization of service offers only occurred in the CAPS and CAPS AD and in a fragile way. Thus, it is necessary to think of strategies such as matrix support, flow chart analyzer and petition network and commitment to seek comprehensive and resolving care in the RAPS for users of alcohol and other drugs.